ANALISIS DAMPAK DIGITALISASI MEDIA SOSIAL INSTAGRAM TERHADAP PENINGKATAN POTENSI WISATA DI DESA WISATA KREBET, KABUPATEN BANTUL - Nurhaliza, Safira; Skawanti, Julia Ratnawulan (Jurnal Pariwisata Indonesia, 2024)
The motivation of this study is to analyze how the digitization of social media, specifically Instagram, has improved the potential for tourism in Krebet Tourism Village, Bantul Regency. With more than 50 craft studios, this community is well-known for its distinctive wooden batik products. Global issues like the COVID-19 pandemic, however, compelled managers and craftspeople to embrace digital media in order to continue marketing and promoting their products. The Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices are utilized to assess primary and secondary data in this descriptive qualitative study. The results serve as the foundation for SWOT analysis, which is used to formulate a plan.the results of the analysis's observations, digitalization—especially Instagram—is crucial for increasing audience reach, increased tourism, and promoting local economic sustainability. By creating interesting content and maintaining an active Instagram account, Krebet Tourism Village was able to draw in visitors, particularly millennials and Gen Z, which enhanced the village's potential for tourism.